METAFORA DAN IDEOLOGI FILM IKLAN MANDIRI SECURITAS - Handriyotopo, H.,; Lastoro, GR Lono; Gustami, SP (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2018)
The Mandiri Securitas advertisement film is a corporate advertisement that contains a persuasive message to increase brand image as a leader in investment in the Stock Exchange or trusted banking investment in Indonesia. The metaphor in the Mandiri Securitas advertisement contains cinematographic images that borrow keris culture to be sided with banking culture. This qualitative descriptive study uses a semiotic approach to appropriate verbal and visual messages from the system of rhetorical marks "Minus One". The content of visual rhetoric and verbal rhetoric on the Mandiri Securitas advertisement was reviewed by Roland Barthes's semiotic theory, because it was considered capable of uncovering the relationship of the sign meaning behind the denotative marker system and connotative markers from the ideology of Mandiri Securitas advertisements with theÂ  theme of empu keris (keris maker). The results of this study prove that the application of the "Minus-One" method is very helpful to find and recognize the roles played by the constituent elements of a film construction. The Mandiri Securitas advertisement film is an example of the appropriation of the tradition world for the benefit of the modern world. The tradition world is not displayed in its entirety as it is, but is displayed partially and determined based on the image of the modern world wants to construct as an imagery form of advertising.Â Keywords: Metaphor, rhetoric, Semiotics, and ideologyÂ